The lifestyle associated with the control of arterial hypertension and diabetes mellitus in a care center in Lima, during the covid-19 pandemic: Estilo de vida asociado al control de hipertensión arterial y diabetes mellitus en un centro de atención en Lima, durante la pandemia de COVID-19 - Callapiña-De Paz, Mariana (2021)
Introduction: Hypertension and diabetes mellitus 2 are prevalent diseases. The COVID-19 pandemic has changed lifestyle and disease control, potentially triggering serious complications. Objectives: To determine the association between lifestyle and the control of chronic non-communicable diseases: arterial hypertension and diabetes mellitus 2 during the COVID-19 pandemic in patients of an Urgent Care Center. Materials and methods: Observational, cross-sectional, and analytical study. A sample of 158 patients, between 30 and 79 years old, was included. Control files and medical records were analyzed, anthropometric values ​​were measured, and lifestyle was evaluated through surveys. Results: 51.3% were male, an average of 61 years, 57.6% with married marital status, and 51.9% with higher educational level. In the multivariate analysis of patients with arterial hypertension, a significant association between the lack of control of the hypertensive disease and an unhealthy lifestyle is evidenced (PR = 2.538; p = 0.000; 95% CI = 1.608-4.006). On the other hand, the diabetic population obtained a significant association between the lack of control of type 2 diabetes mellitus with an unhealthy lifestyle (PR = 5.498; p = 0.013; 95% CI = 1.440-20.995), in addition to the prevalence of glycemic lack of control in patients with abnormal abdominal girth it was 1.6 times more than in people with normal abdominal girth (PR = 2.623; p = 0.038; 95% CI = 1.057-6.508). Conclusions: Lifestyle is significantly associated with the control of arterial hypertension and diabetes mellitus. There is a significant association between abdominal circumference and control of type 2 diabetes mellitus.